Basic Requirements for Public Participation in Kenya’s Legal Framework - Nizam, Rabya; Muriu, Abraham Rugo; International Budget Partnership (World Bank Group, Washington, DC, 2015)
Kenya has embarked on a highly ambitious decentralization that seeks to fundamentally change the relationship between government and citizens under the 2010 Constitution. The Constitution and new legal framework place a strong emphasis on strengthening public participation.